Effect of sucrose and Cytokinin on in vitro Mircrorhizome induction of ginger (Zingiber ofcinale Roscoe cv. Tambunan) - Ling, Ee Chuwan (Universiti Malaysia Sabah, 2017)
Ginger is a spice plant which had been proven to bring various uses and benefits to people. Although ginger has a very high demand in the market, but the production of ginger especially Tambunan ginger (Zingiber officinale Roscoe cv. Tambunan) rarely satisfy the market demand. This study was carried out at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah from March 2016 until October 2016 to investigate the effect of sucrose (30, 60, and 90 g/L) and cytokinin (6 and 9 mg/L) on in vitro microrhizome induction in ginger (Zingiber officinale Roscoe cv. Tambunan). The treatments were arranged in completely randomized design (CRD) with ten replications. Data collected was analysed using two-way Analysis of Variance (ANOVA) at 5% significance level. The significance between means were compared by Tukey at 5% significant level. All the vegetative growth parameters such as leaf number, root number, shoot number and shoot height showed no significant differences as affected by the interaction of sucrose and cytokinin. As for the microrhizome parameters, it was found out that the interaction of sucrose and cytokinin had significant differences on the number microrhizome formation, total microrhizome weight, total number of buds and number of buds per microrhizome except for the average weight of microrhizome. The treatment 60 g/L sucrose concentration and 6 mg/L BAP produced the highest number of microzhome (7.1), the heaviest total microrhizome weight (2.897g) and microrhizome with the highest total number of buds (35). As for the highest number of buds per microrhizome, treatment 30 g/L sucrose with 9 mg/L BAP had the highest record of 8.3. The production of microrhizome in ginger was found to be influenced by several factors such as sucrose concentration and BAP rate. The usage of treatment 60 g/L sucrose and 6 mg/L BAP can provide solution for the lack of planting materials in ginger. The future study is recommended to include range between 60 g/L to 80 g/L sucrose concentration in order to know the precise treatment that cultured the most number of microrhizome in ginger.